PENGARUH PERSONAL SELLING, DIRECT SELLING DAN HUBUNGAN MASYARAKAT TERHADAP KEPUASAN NASABAH Studi Kasus pada BMT UGT Sidogiri KCP Kanigoro Blitar (An-Nisbah: Jurnal Ekonomi Syariah, 2016)
The purpose of this study was to test there any infuence of personal selling, direct selling and public relations signifcantly to customer satisfaction in BMT UGT Sidogiri KCP Kanigoro Blitar. The results show that personal selling, direct selling and public relations together have a signifcant effect on customer satisfaction. count by using T test personal selling unknown variables have positive and signifcant impact on customer satisfaction with the Sig. 0,000. Variable direct selling has a positive impact and no signifcant effect on customer satisfaction in BMT UGT Sidogiri KCP Kanigoro Blitar with the Sig. 0.423 and variable public relations has a positive impact and no signifcant effect on customer satisfaction in BMT UGT Sidogiri KCP Kanigoro Blitar with the Sig. 0.247.Keywords : personal selling, direct selling, customer satisfaction